Bandwidth enhancement of spiral antenna with defected ground structure - Mohamed, Mohamed Osman (2018)
In wireless communications systems, harmonics and unwanted frequency other than designed one becomes a dominant factor in limiting quality and capacity of transmitted or received signal. Rectangular spiral antenna (RSA) is designed in order to obtain the required parameter responses at 2.45 GHz for Wifi application. The proposed antenna is excited through the coaxial feed line which is connected from the ground of the antenna. RSA of length 16cm and width 20cm is designed on the substrate dielectric material FR-4 having dielectric constant er = 4.3 and thickness 1.6 mm. Conventional rectangular spiral antenna without DGS has very low bandwidth. This antenna has 64.8MHz which is very low and the fractional percentage is 2.63%. The defect ground structure (DGS) has gained much attention over the last few years for its ability to enhance the bandwidth and gain. After applied DGS the bandwidth enhanced to 245MHz which is very high compared to the conventional antenna. The antenna without DGS has multiple frequencies which are 1.3734, 2.0886 and 2.6538 other than the desired frequency.The DGS also effectively suppress harmonics frequencies of the spiral antenna, shows a better result compared to the conventional antenna. It effectively suppressing spurious frequency and reduces the amplitude of the unwanted multiple bands since the antenna radiates only one resonating frequency.